Fire incident at a refinery in West Malaysia: the causes and lessons learned - Shaluf, Ibrahim M; Ahmadun, Fakhrul-Razi; Said, Aini Mat (Elsevier, 2003)
Refineries are major hazard installations (MHI) which possess large quantities of hazardous substances. Refineries are characterized by high complexity and tight-coupled organization. Due to the high complexity and level of interaction among subsystems, designers and operators are unable to predict failures at the refinery units. The world has seen many incidents in refineries through leakage, fire and explosions. The consequences of the accidents sometimes extend beyond the boundary of the property and reach the neighboring residents. This paper reviews refinery incidents worldwide and also outlines the causes of a fire incident at a refinery in West Malaysia and the lessons learned.